Geração de carga de trabalho transiente para aplicações de e-commerce multicamadas - nior, Lourenço Alves Pereira Jú; Souza, Flávio Luiz dos Santos de; Mamani, Edwin Luis Choquehuanca; Monaco, Francisco José (Anais do Workshop em Clouds e Aplicações (WCGA), 2017)
Considering the great adoption of cloud computing as operational platform by e-commerce retailers and its dynamical environment setup, workload on this systems is basically time-varying. Caused by user bahavioral patterns, as well as flash crowds and virals, the system trespass differents operational regions leading to transients. In a scenario where transients is commonplace, the proper study of this phenomenon is important. Although, in spite of many benchmarks whose purpose is load systems with synthetic work, it is not usual to find an interface to express how workload must change on the fly during an experimental execution, as a matter of concern. Thus, this papers presents the implementation of a time-varying workload generator as an extension of the Bench4Q tool. The results point towards the importance of applying such kind of performance tests by allowing the apprisal of system's transients when using IBM DB2 and PostgreSQL, revealing the dynamic behavior of the performance metric response time.